Factors Affecting Fintech Acceptance: A Qualitative Case Study in Sri Lanka - Piyananda, S.D.P.; Aluthge, D.C.P. (Colombo Economic Journal, 2023)
With the COVID-19 outbreak, an increasing trend to shift toward cashless transactions in Sri Lanka is witnessed. With the emergence of JustPay, LankaQR, Genie, etc. most of the barriers in the local Fintech industry have been removed. However, empirical studies have revealed that even though there has been a strong implementation of digital payment methods in the country, their adoption by consumers is relatively low. This study analyzes the experience of Fintech industry players in Sri Lanka in promoting Fintech solutions in the country, particularly identifying the factors affecting Fintech acceptance by consumers. This study employed a qualitative case study approach with five CEOs from Fintech firms in Sri Lanka. Semi-structured interviews were conducted, and data was analyzed thematically. The findings of the study revealed that consumers’ awareness about Fintech services, Fintech’s ability to serve the real-life needs of consumers, consumers’ trust, availability of digital infrastructure facilities of the country, the convenience offered by the products are the main factors that directly affect Fintech acceptance. All the CEOs who were interviewed highlighted the importance of building consumer trust and awareness.
Keywords: Cashless; Fintech acceptance; Digital payments; Qualitative study